PENGARUH CAREER PATTERNS TERHADAP ORGANIZATIONAL PERFORMANCE: PERAN MEDIASI NEUTRALITY - Said Mitra Setia Irawan; Adi Rahmat; Agus Seswandi (Indragiri Research Center (ingreat), 2025)
This study will analyze how career patterns applied in ASN organizations can affect their performance, and how neutrality can function as a mediator in the relationship. Through a better understanding of these dynamics, it is expected to provide useful insights for policy makers and organizational leaders in designing more effective strategies. The study is a type of quantitative descriptive research with a causal research design with a population of 7,036 ASN from Indragiri Hilir district with a sample in this study of 150 people using the heir method. Data collection techniques using questionnaires and distribution using google forms. The data analysis tool in this study is Structural Equation Modeling (SEM) processed using SmartPLS 32.9 for data processing. From the findings of this study, it was found that career patterns have a positive and insignificant effect on organizational performance (hypothesis 1 is rejected), career patterns are positive and significant on neutrality (hypothesis 2 is accepted), neutrality is positive and significant on organizational performance (hypothesis 3 is accepted) and career patterns have a positive and significant effect on organizational performance through neutrality (hypothesis 4 is accepted).